Effect of Subjective Norm on Consumers' Purchase Intention Towards Counterfeit Apparel Products: Does Level of Formal Education Matter? - Mbura , Sophia (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2023)
This study investigated the moderating effect of the level of formal education on the subjective norm and purchase intention of consumers towards counterfeit apparel products in Tanzania. The study utilized a survey strategy during data collection and involved 315 respondents as a sample size. The researcher employed Structural Equation modeling technique using AMOS software for data analysis. The results indicated that subjective norm had a positive and significant effect on purchase intention of counterfeit apparel. The results showed no statistical differences between subjective norm and purchase intention of counterfeit apparel products in less and high levels of formal education consumers. The study concluded that subjective norm is the key predictor of consumers’ purchase intention of counterfeit apparel products. The study also concluded that the level of formal education had no moderating effect on the relationship between subjective norm and purchase intention counterfeit apparel. Thus, the study recommends that future researchers to consider other predictors and moderating variables to investigate consumers purchase intention of counterfeit apparel products in different settings.